2005
DOI: 10.1021/jp052492d
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved Measurements of the Photolysis and Recombination of Adenosylcobalamin Bound to Glutamate Mutase

Abstract: Femtosecond to nanosecond transient absorption spectroscopy is used to investigate the photolysis of 5'-deoxyadenosylcobalamin (coenzyme B12, AdoCbl) bound to glutamate mutase. The photochemistry of AdoCbl is found to be inherently dependent upon the environment of the cofactor. Excitation of AdoCbl bound to glutamate mutase results in formation of a metal-to-ligand charge transfer intermediate state which decays to form cob(II)alamin with a time constant of 105 ps. This observation is in contrast to earlier m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
119
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(128 citation statements)
references
References 57 publications
8
119
1
Order By: Relevance
“…For each data set a single principle component was identified, the principle kinetic of which was fit to a sum of four exponentials ( Figure S3). The kinetic data from the exponential fits given in Table 1 are comparable to those observed in glutamate mutase, [30] and appreciably different from free AdoCbl. [28] The value for k 1 in water corresponds to a time constant of 178 fs, which is near the instrument response function of ca.…”
Section: Angewandte Chemiesupporting
confidence: 64%
See 1 more Smart Citation
“…For each data set a single principle component was identified, the principle kinetic of which was fit to a sum of four exponentials ( Figure S3). The kinetic data from the exponential fits given in Table 1 are comparable to those observed in glutamate mutase, [30] and appreciably different from free AdoCbl. [28] The value for k 1 in water corresponds to a time constant of 178 fs, which is near the instrument response function of ca.…”
Section: Angewandte Chemiesupporting
confidence: 64%
“…[29] There are also clear differences from free AdoCbl in the early-time spectra, which again resemble those in glutamate mutase where they are attributed to excited metal-to-ligand charge transfer states. [30] The transient difference spectra from the EAL holoenzyme were analyzed for principle components using single value decomposition (SVD). For each data set a single principle component was identified, the principle kinetic of which was fit to a sum of four exponentials ( Figure S3).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…7 There is a large amount of evidence in favour of Path 1 and this path is favoured by Jost and Drennan and colleagues 7 . Cage effects by proteins have been previously observed in the AdoCbl-dependent glutamate mutase 45,46 and in the MeCblbinding domain of methionine synthase 47 . In addition to thermolysis of AdoCbl and adenosylcobinamide [39][40][41] , homolytic fission followed by radical-mediated β-elimination is well documented in alkylcobalamins and alkylcobinamides [48][49][50] .…”
Section: Carh-bound Adocbl: Products Of Photolysis and The Co-c Bondmentioning
confidence: 85%
“…56,58,65 In contrast, the photolysis of AdoCbl was found to be wavelength independent resulting in a creation of a geminate radical pair within 100-130 ps at room temperature. 57,59,62 The same studies for ethyland n-propylcobalamin indicated the formation of radical pair when samples were excited at both 400 and 520 nm but the rapid dissociation contribution was mainly observed following the higher energy excitation. At the same time, the short-lived S 1 state, which could be a spectral counterpart to the one occurring after MeCbl excitation, was more prominent following the excitation at 520 nm.…”
Section: Introductionmentioning
confidence: 79%
“…The high reactivity of cob(I)alamin prevents a detailed structural characterization and spectroscopic techniques are therefore important tools for gaining in- 58,62,65 it has been proposed that S 1 intermediate state in CNCbl is best described as π → d z 2 Co ligand-to-metal charge transfer (LMCT). 64,65 In the present chapter the electronic and structural properties of low-lying excited states of CNCbl were studied by means of time-dependent density functional theory (TD-DFT).…”
Section: Discussionmentioning
confidence: 99%